Implications of Geographical Indications for Rice in Kerala - Radhika A.M (Department of Agricultural Economics,College of Horticulture, 2019)
The present study entitled “Implications of Geographical Indications for rice in Kerala” was conducted with the objectives of assessing the impact of GI rice on income and welfare of the producer households, identifying the major supply chains, evaluating the institutional innovations in the supply chains, proposing viable supply chain options and examining the export prospects and market access of the registered GI rice. The rice GIs of Kerala viz., Navara, Pokkali, Jeerakasala, Gandhakasala, Palakkadan Matta and Kaipad were selected for the study. From each of the six categories, fifty farmers each were randomly selected making a total sample of 300 farmers. Data was also collected from market intermediaries and producer societies in each GI tract. Cost-return structure was worked out for the selected GI rice using percentage analysis and cost concepts. The highest cost of cultivation (Cost C2) was found in the case of Jeerakasala (`.131082/ha) followed by Gandhakasala (`.127308/ha). The highest average yield was realised for Palakkadan Matta (4498 kg/ha) and lowest yield was realised for Pokkali (1835 kg/ha). Accordingly, the cost of production was highest for Pokkali and lowest for Palakkadan Matta. The highest average gross income of `.155568/ha was obtained for Navara while it was lowest for Pokkali (`.75036/ha). The net income and BC ratio indicated that farming was a loss making business for farmers growing Pokkali, Jeerakasala and Gandhakasala, especially when the value of the family labour, land value and managerial cost were imputed and accounted in the cost. The BC ratio worked out to be more than one in the case of Navara (1.31), Palakkadan Matta (1.05) and Kaipad (1.02). The producer’s performance was assessed using one output and four inputs using DEA model. All the GIs showed low technical efficiency (<40 per cent). The estimated mean technical efficiency for producers of Gandhakasala was highest (90.5 per cent) and the least efficient producers were seen in Pokkali. The scale efficiency results showed that all the GIs were scale inefficient which could be attributed to low operational scale of units. The impact of GI on income and welfare of producer households was measured using the method of treatment effect analysis. The average treatment effects were worked out for the outcome variables; yield per hectare, net income, marketed surplus, and value of marketed surplus. Even though the yield of Navara was comparatively lower than that of Palakkadan Matta, Jeerakasala and Gandhakasala, the net income, marketed surplus and value of marketed surplus were higher for Navara. The yield per hectare was higher for Jeerakasala when compared to Gandhakasala while the net income, marketed surplus and value of marketed surplus were higher for Gandhakasala. Palakkadan Matta recorded the highest yield among these categories, but net income, marketed surplus and value of marketed surplus were comparatively low. The marketed surplus of Pokkali was comparatively higher than Kaipad even though yield, net income and value of marketed surplus were comparatively very less. Three marketing systems were prevalent in the study area. Some farmers market paddy through market intermediaries, some resource rich farmers cultivate and process their produce to meet the requirements of high end consumers and other resource poor farmers sell off their produce to local consumers after processing in nearby mills. The Palakkadan Matta farmers were marketing their produce through Supplyco at the rate of `.22.50/kg. Institutional Analysis and Development Framework (IAD) was used to explore the performance of GIs. Efforts were made for studying the institutional innovations strategies for enhancing profitability and effectiveness of the GI mechanism, to propose viable supply chain options and to examine the export prospects and market access of the registered GI rice. Producer societies play a lead role in the registration process of a GI. The other actors include GI registry, IPR cell, KAU and Producers of the respective GIs. The average prices of all these speciality rice have increased after GI registration. Group-farming can be adopted as an option to bring more area under production. Despite having ample scope for enhancing the income of farmers through diversification, lack of facilities for value addition is a major hurdle. Processing units and storage facilities should be established near major producing areas to overcome this problem. Taking advantage of the GI status, efforts are to be made for marketing GI products as a premium priced branded organic produce. An effective institutional arrangement should be constituted to ensure quality production and efficient marketing of GI rice.